1975
DOI: 10.1017/s0021859600062328
|View full text |Cite
|
Sign up to set email alerts
|

An equation to predict the leaching of surface-applied nitrate

Abstract: The fraction (/) of surface-applied nitrate leached below any depth h cm in a uniform soil profile may be calculated from the equation ,/100)/ where P is the quantity of water draining through the soil (in cm) and V m is the percentage volumetric field capacity. The fraction of nitrate retained is then (1-/). This equation has been tested using published data. Values of h corresponding to the mean displacement (/ = 0-5) were calculated for a wide range of soil and weather conditions and the results compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
1
1

Year Published

1976
1976
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 16 publications
2
51
1
1
Order By: Relevance
“…Periodic checks of the nitrogen content can be made by chemical analysis, but during wet spells, when rapid changes in nitrogen levels often occur, more frequent estimates of nitrate losses are necessary so that prompt remedial action can be taken. In a previous paper (Burns, 1975) an equation was derived for predicting the leaching of surface-applied nitrate. In this paper-leaching equations have been devised for nitrate incorporated uniformly to a limited depth, and for nitrate distributed uniformly throughout a soil profile.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Periodic checks of the nitrogen content can be made by chemical analysis, but during wet spells, when rapid changes in nitrogen levels often occur, more frequent estimates of nitrate losses are necessary so that prompt remedial action can be taken. In a previous paper (Burns, 1975) an equation was derived for predicting the leaching of surface-applied nitrate. In this paper-leaching equations have been devised for nitrate incorporated uniformly to a limited depth, and for nitrate distributed uniformly throughout a soil profile.…”
Section: Introductionmentioning
confidence: 99%
“…If nitrate is initially incorporated uniformly to a depth of w cm, then x = h -^w (where h 2s w); if nitrate is distributed uniformly throughout the whole profile, then x = \h. For surface-applied nitrate x = h (Burns, 1975).Observed mean displacements in published experiments have been compared with predictions from the equations and from equations in which the. mean movement of nitrate and water are assumed equal.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As part the initial feasibility study, first-order modeling and soil column studies were performed to assess the potential for transport of NP through the vadose zone to the groundwater table. The Burn Model was selected as an empirical transport model that can account for preferential flow (Burns, 1975). In the late 1970s an empirical single-parameter equation was proposed to represent the flow of water and solutes through soils.…”
Section: Edc Transport Modelmentioning
confidence: 99%
“…The time sequence of the leaching loss is an important factor in determining the temporal variability and range of variation in stream N concentrations. Various possible models for describing the leaching in NIRAMS were considered, including those suggested by Lord and Anthony (2000), and a combination of the vertical Burns (1975) with a steady state model of horizontal flow to tile drains (Van Ommen, 1985). Tests on these approaches suggested that they might not be the most appropriate for this application.…”
Section: Calculation Of N Leachingmentioning
confidence: 99%